1998
DOI: 10.1074/jbc.273.40.25751
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Metabolism of Valine to Isobutyl Alcohol in Saccharomyces cerevisiae

Abstract: The metabolism of valine to isobutyl alcohol in yeast was examined by 13 C nuclear magnetic resonance spectroscopy and combined gas chromatography-mass spectrometry. The product of valine transamination, ␣-ketoisovalerate, had four potential routes to isobutyl alcohol. The first, via branched-chain ␣-ketoacid dehydrogenase to isobutyryl-CoA is not required for the synthesis of isobutyl alcohol because abolition of branchedchain ␣-ketoacid dehydrogenase activity in an lpd1 disruption mutant did not prevent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 20 publications
1
136
0
Order By: Relevance
“…It should also be noted that the slightly elevated end of fermentation fusel levels observed in the trials conducted under optimized conditions are consistent with the observed increase in FAN consumption, as all of the fusels specified are by-products of the catabolic valine pathway from ␣-ketoisovaleric acid. 18,52 Overall, the key flavour metabolites were not negatively influenced by the altered process conditions. wort.…”
Section: Timing Of Initial Cell Division (3-l Bench-scale)mentioning
confidence: 99%
“…It should also be noted that the slightly elevated end of fermentation fusel levels observed in the trials conducted under optimized conditions are consistent with the observed increase in FAN consumption, as all of the fusels specified are by-products of the catabolic valine pathway from ␣-ketoisovaleric acid. 18,52 Overall, the key flavour metabolites were not negatively influenced by the altered process conditions. wort.…”
Section: Timing Of Initial Cell Division (3-l Bench-scale)mentioning
confidence: 99%
“…These aldehydes can be reduced to their corresponding branched alcohol (2-methyl-butanol, 3-methyl-butanol and 2-methyl-propanol) by action of the ADH enzyme, which uses NAD(P) + as a cofactor (30,140,143,145,147). The transformation of amino acids into alcohols is known as the Ehrlich pathway, in which the key enzymes are transaminases, decarboxylases and dehydrogenases (148).…”
Section: Mcintoshmentioning
confidence: 99%
“…The transformation of amino acids into alcohols is known as the Ehrlich pathway, in which the key enzymes are transaminases, decarboxylases and dehydrogenases (148). Branched aldehydes can also be oxidized to their corresponding branched fatt y acid (2-methyl-butanoic, 3-methyl-butanoic and 3-methyl-propanoic) by the action of aldehyde dehydrogenase (AldDH) (30,140,143,147), which uses NAD(P)H as a cofactor.…”
Section: Mcintoshmentioning
confidence: 99%
See 1 more Smart Citation
“…K-Ketoisovalerate and K-keto-L-methylvalerate show similar patterns towards NaCl and pH as K-ketoisocaproate. Cross talk between catabolic and anabolic reactions of the branched-chain amino acid metabolism may explain the formation of the di¡erent keto acids and fusel alcohols, as described by Dickinson et al [6,7]. Van der Sluis [16] has not reported the accumulation of these K-keto acids, which are not derived from leucine.…”
Section: Substrate Consumption and Formation Of Extracellularmentioning
confidence: 99%